Diacerein: Advantages and disadvantages - Andrei Evgenyevich Karateev (Современная ревматология, 2014)
Diacerein (DR) is a medication from a group of symptomatic slow-acting agents (chondroprotectors), which has an original mechanism of action and is widely used in Russia and many countries in the world to treat osteoarthrosis (OA). The ability of DR to affect its major symptoms and progression has been shown in a series of well-organized clinical trials. However, the supervisory health bodies of the European Union have presently made a decision to restrict the use of DR, which is associated with the fact that the viewpoint of this drug's safety level has been changed. The case in point is gastrointestinal complications (diarrhea) and hepatotoxic reactions, which may be caused by DR treatment. This review considers the results of the most known clinical trials of DR, gives basic data on its adverse reactions, and assesses prospects for using its new generic drugs.